My heart is like a zoo - Hall, Michael, 1954- (New York : Greenwillow Books, 2010)
Depicts in rhyming text how love can be many different things, such as eager as a beaver, steady as a yak, or silly as a seal.
Booklist
2.9
K-3.
K-3
Keywords: Love -- Juvenile fiction; Zoo animals -- Juvenile fiction; Love -- Fiction; Stories in rhyme; Zoo animals -- Fiction; Love -- Fiction; Stories in rhyme; Zoo animals -- Fiction; Picture books for children